Mosaicism of alpha-synuclein gene rearrangements: Report of two unrelated cases of early-onset parkinsonism - Perandones, Claudia (2014)
In genetics, the term mosaicism describes the situation in which groups of cells have a different genetic composition to other cells in an organism. Somatic gene rearrangements due to multiplication or deletion of genes (copy number variation) and/or sections of chromosomes can lead to mosaicism. The presence of multiple copies of the alpha-synuclein gene (SNCA) is known to be associated with Parkinson´s disease (PD) and the severity of symptoms increases with the number of copies of the gene [1]. While the features of PD associated with duplication of SNCA are usually (but not always) typical of the condition [2] and [3], patients with triplicate copies have atypical features, including rapidly evolving symptoms, severe cognitive impairment, limited response to levodopa, more severe symptoms of dementia and more frequent urinary incontinence [2]. A lack of studies of mosaicism in PD illustrates that the prevalence and mechanism of these rearrangements have not yet been elucidated.